EFFECT OF DIFFERENT PACKAGING MATERIALS ON STORAGE QUALITY AND SENSORY EVALUATION OF PIGEON PEA DHAL - Mohammod Jeelani (The Journal of Research ANGRAU, 2026)
Post-harvest losses of pulses primarily result from improper handling and storage conditions. A study was conducted during August 2023 to March 2024 aimed to identify suitable packaging material for storing pigeon pea dhal by evaluating quality attributes and sensory characteristics. Fresh pigeon pea dhal (cv. LRG 52) was stored for 8 months in five different packaging materials: High Density Polyethylene (HDPE), Jute bags, Low Density Polyethylene (LDPE), Biaxially Oriented Polypropylene (BoPP) and Polyethylene Terephthalate (PET) containers, under ambient temperature of 21-37°C and relative humidity (RH) of 26-90 %. Quality parameters such as insect infestation, grain damage, weight loss, moisture content, and cooking time were recorded for every two months. The moisture content (%w.b.) of stored pigeon pea in different packaging materials ranged from 9.13-10.86% in Jute bags, 9.13-9.27% in HDPE, 9.13-9.66% in LDPE, 9.13-8.87% in PET and 9.13-8.94% in BoPP. In HDPE, LDPE and Jute bag, the final moisture content was higher than the initial levels indicating net loss in moisture content, while PET and BoPP showed the opposite trend. The protein content decreased in all packaging materials over the storage period. Further, the grain damage of stored pigeon pea in different packaging material ranged from 0.14-0.33% in HDPE, 0.23-1.05 % in LDPE and 0.34-1.15 % in Jute bags. Grain damage by insects was not detected in pigeon pea samples stored in PET and BoPP material throughout the storage period of 240 days. But infestation was observed after 180 days of storage in HDPE and after 60 days in pigeon pea stored in LDPE and jute bags. The cooking time was less than 16 min for all the pigeon pea samples. Sensory analysis was conducted for non-infested samples and the data was evaluated using fuzzy logic. BoPP proved to be superior packaging material for maintaining the sensory quality of pigeon pea dhal, especially up to 60 days of storage. Taste emerged as the most influential factor in consumer preference, highlighting the importance of preserving flavour during storage. BoPP, with its laminated layers and high barrier properties, retained flavour effectively